2022
DOI: 10.4269/ajtmh.21-1195
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Management, Community Engagement, and Sustainability of the Subnational Response to Accelerate Malaria Elimination in Namibia

Abstract: Leadership and management skills are critical for health programs to deliver high-quality interventions in complex systems. In malaria-eliminating countries, national and subnational health teams are reorienting strategies to address focal transmission while preventing new cases and adapting to decentralization and declines in external financing. A capacity-strengthening program in two regions in Namibia helped malaria program implementers identify and address key operational, political, and financial challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies have identified factors such as cross-border transmission from neighboring countries, insecticide resistance in mosquito vectors, limited access to healthcare services in rural areas, and resource constraints as barriers to malaria control efforts in Namibia. However, there are also opportunities for strengthening malaria control, including leveraging lessons learned from other countries, enhancing collaboration and knowledge sharing, and advocating for increased political commitment and funding for malaria elimination (Chung et al, 2022). One prominent global program aimed at eliminating malaria is the "Global Malaria Programme" (GMP) initiated by the World Health Organization (WHO).…”
Section: Challenges and Opportunities In Namibiamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified factors such as cross-border transmission from neighboring countries, insecticide resistance in mosquito vectors, limited access to healthcare services in rural areas, and resource constraints as barriers to malaria control efforts in Namibia. However, there are also opportunities for strengthening malaria control, including leveraging lessons learned from other countries, enhancing collaboration and knowledge sharing, and advocating for increased political commitment and funding for malaria elimination (Chung et al, 2022). One prominent global program aimed at eliminating malaria is the "Global Malaria Programme" (GMP) initiated by the World Health Organization (WHO).…”
Section: Challenges and Opportunities In Namibiamentioning
confidence: 99%
“…Factors such as distance to health facilities, transportation barriers, and socioeconomic factors may prevent individuals from seeking timely care. Sustaining community engagement and promoting behavior change remain essential for effective malaria control and prevention (Chung et al, 2022). Ensuring consistent use of preventive measures such as bed nets, seeking prompt treatment for fever, and adhering to treatment regimens are crucial but can be challenging to achieve.…”
Section: Challenges In the Elimination Of Malaria In Namibiamentioning
confidence: 99%